Is Microsurgery Necessary in Grade 3 Varicocele? - Kalkan, Mehmet; Yalcinkaya, Soner; Etlik, Omer; Sahin, Co?kun (Urology Journal, 2011)
Purpose: To compare the results of microsurgical and naked eye varicocelectomy in patients with grade 3 varicocele. Materials and Methods: This study was conducted on 84 patients with grade 3 varicocele, between 2007 and 2009. Patients were randomized into two groups, equal in number. Thereafter, microsurgical varicocelectomy was performed in the first group, while the other group underwent naked eye varicocelectomy. Groups were compared in terms of operation duration, number of ligated internal and external spermatic veins, early and late postoperative complications, and postoperative color Doppler ultrasonography findings. Parametric and nonparametric values were compared using Student’s t test and Chi-Square test, respectively. Results: The mean duration of surgery was 19 ± 2.3 minutes (range, 12 to 25 minutes) in the naked eye surgery group and 43 ± 3.9 minutes (range, 25 to 75 minutes) in the microsurgery group (P = .008). The number of ligated internal and external spermatic veins, the incidence of early and late postoperative complications, and color Doppler ultrasonography findings were not significantly different between the two groups (P = .12, P = .09, P = .17, and P = .22, respectively). Conclusion: In patients with grade 3 varicocele, microsurgery and naked eye surgical methods proved similar results in terms of success and complications. Because the operation time of the classical varicocelectomy is significantly shorter, it may be preferred in this subset of patients.